PHYLOGENETIC RELATIONSHIPS AMONG POPULATIONS OF THE RED VOLE MYODES (= CLETHRIONOMYS) RUTILUS PALLAS, 1779 IN THE NORTHERN PRIOKHOTYE AND KOLYMA REGIONS - V. V. Pereverzeva; A. A. Primak; E. A. Dubinin (Вавиловский журнал генетики и селекции, 2015)
The goal of the work was the determination of phylogenetic relationships in red vole associations of the Northern Priokhotye and Kolyma regions on the base of analysis of partial mtDNA cytb gene sequence polymorphism in some Myodes (Сlethrionomys) rutilus populations of Northeastern Asia and Alaska. Genetic analysis allowed the different levels of differentiation among red vole populations from the basins of Kolyma and Yama rivers and the suburbs of Magadan city to be determined. The haplotypes of red vole in the populations from islands of Tauysk Bay, the continental part of the Northern Priokhotye region, and the Kolyma region belong to the eastern lineage with the basal B1 gene variant. The haplotypes of representatives of populations from Kamchatka, Alaska, and Matykil and Sakhalin islands belong to the Beringean lineage. The Siberian samples differ significantly from the above lineages, being an interlink between them. The differentiation of red vole populations in the region and phylogenetic relationships among groups appear to be a consequence of certain features of the species expansion to the northeast in the Late Pleistocene. The first wave of red vole migrated to North America across the Bering land bridge. Presently the descendants of this wave inhabit Alaska, Sakhalin, Kamchatka, and Matykil island. For the second time, the red vole entered the region at the end of the Late Pleistocene. During the second wave of dispersal, red voles from the eastern branch occupied the drainage area of the Kolyma river and the coast of the Sea of Okhotsk together with some neighboring islands.